Serological Evidence of Exposure to Peste des Petits Ruminants in Small Ruminants in Rwanda - Shyaka, Anselme; Ugirabe, Marie Aurore; Wensman, Jonas Johansson (Frontiers in Veterinary Science, 2021)
Peste des Petits Ruminants (PPR) status in Rwanda is unknown, despite its prevalence in neighboring countries. Serum samples were collected and analyzed using a commercial ELISA, to detect antibodies to PPR virus (PPRV). Sixty-eight samples (14.8%, 95% Confidence Interval (CI): 11.7-18.4) were seropositive for PPR, of which 17.4% (95%CI: 11.6-24.6; 25/144) were from sheep, whereas 13.6% (95% CI: 10.0-17.9; 43/316) were from goats. Seropositivity ranged from 8.9% to 17.3% (goats) and from 10.5% to 25.8% (sheep) in sampled districts. Seropositivity was slightly higher in males than females in both goats (15.7% vs. 12.4%) and sheep (17.7% vs. 17.1%), and were significantly marked in goats and sheep aged more than 15 months (goats: 17.9%, 95% CI: 12.9-24.0; sheep: 22.2%, 95% CI: 14.1-32.2) than those between 6 and 15 months (goats: 6.1%, 95%CI: 2.5-12.1; sheep: 9.3%, 95% CI: 3.1-20.3). Sampling was non-randomized and results are not representative of the true prevalence of PPR antibody in small ruminants. Thus, data does not allow to fully discuss the findings beyond the presence/absence certitude. The presence of specific antibodies to PPRV may, however, be linked to one or a combination of following scenarios: 1) prevalence and persistence of PPRV in sampled regions with low level of clinical cases and/or mortalities that go unnoticed; 2) introduction of PPRV to herds through transboundary movements. and/or 3) events of disease outbreaks that are underreported by farmers and veterinarians. Further studies using robust sampling methods and integrating livestock and wildlife are needed, to fully elucidate PPR epidemiology in Rwanda.